PENERAPAN M-BANKING DALAM MENINGKATKAN JASA, LAYANAN PERBANKAN DI BANK SYARIAH INDONESIA - Kurnia, Agnes; Muhammad Iqbal Fasa; Is Susanto (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The development of digitalization technology in the banking sector, including sharia banking in Indonesia, has undergone changes. One innovation that is developing rapidly is mobile banking (m-banking). This allows customers to access banking services quickly and efficiently via their mobile devices. The purpose of this research is to find out how the implementation of mobile banking at PT Bank Syariah Indonesia can improve company service and services. This research uses a document study and literature study approach. The data analysis method used is a qualitative method as a research method that describes descriptively the application of M-banking in improving services at PT Bank Syariah Indonesia. The research results show that using M-banking can simplify financial and non- financial transactions, and make customers interested in using it. However, there are still challenges in terms of technical capacity and infrastructure reliability that need to be improved as a whole. The introduction of m-banking at Bank Syariah Indonesia has great potential to increase competitiveness and strengthen the role of Sharia Banking in supporting financial inclusion in Indonesia.